Kesehatan Reproduksi Remaja Putri di Pondok Pesantren Sidoarjo Jawa Timur - Nisa Mairo, Queen Khoirun; Rahayuningsih, Sri Endah; Purwara, Benny Hasan (Faculty of Medicine, Universitas Padjadjaran, 2015)
terkait kesehatan reproduksinya. Remaja lebih banyak menghabiskan waktunya di sekolah. Pondok pesantren merupakan model pendidikan yang bercirikan asrama dengan pola interaksi 24 jam dengan teman sebaya. Penelitian ini bertujuan menganalisis faktor yang berhubungan dengan kesehatan reproduksi remaja putri di pondok pesantren. Penelitian ini dilakukan pada 100 remaja putri Pondok Pesantren Darul Falah Pusat pada kurun waktu September−Oktober 2012 dengan menggunakan kuesioner yang telah teruji validitas dan reliabilitasnya. Variabel pengetahuan, sikap, komunikasi orangtua, komunikasi guru, komunikasi teman sebaya, dan sumber informasi sebagai independen, sedangkan kesehatan reproduksi sebagai dependen. Data dianalisis secara univariabel, bivariabel, dan multivariabel. Hasil penelitian menunjukkan remaja yang bermasalah dalam kesehatan reproduksi sebanyak 68%. Kesehatan reproduksi remaja terdapat hubungan bermakna dengan faktor pengetahuan (p=0,022), sikap (p=0,002) dan komunikasi teman sebaya (p<0,001), tetapi tidak terdapat hubungan bermakna terhadap kesehatan reproduksi remaja pada komunikasi orangtua (p=0,655), komunikasi guru (p=0,833), dan sumber informasi (p=0,532). Faktor yang paling berhubungan dengan kesehatan reproduksi remaja putri di pondok pesantren adalah komunikasi teman sebaya (p=0,001). Simpulan, masalah kesehatan reproduksi di pondok pesantren masih tinggi dengan pengetahuan mengenai kesehatan reproduksi masih rendah, sikap terhadap kesehatan reproduksi kurang, dan faktor yang paling berhubungan adalah komunikasi teman sebaya. [MKB. 2015;47(2):77–83]Kata kunci: Kesehatan reproduksi remaja, lingkungan, pengetahuan, pondok pesantren, sikapReproductive Health of Adolescent Girls in Islamic Boarding School Sidoarjo East JavaAbstractReproductive organ maturation process in adolescence is often prone to health issues. Adolescents spend more time in school, especially when they study in an islamic boarding school. Islamic boarding school is an educational model which is characterized by a dorm with 24 hour interaction pattern among peers. This study aimed to analyze factors associated with adolescent reproductive health in Islamic boarding school female students. This study was conducted on 100 adolescent girls in Darul Falah Center Islamic boarding school during September to October 2012 using questionnaires with proven validity and reliability. Knowledge, attitudes, parent communication, teacher communication, peer communication, source of information were used as the independent variables and reproductive health was used as the dependent variable. All variables were analyzed ini univariabel, bivariable, and multivariable manners. The results of this study show that 68% adolescents had reproductive health problems. There was a significant relationship between knowledge (p=0.022), attitude (p=0.002) and peers communication (p<0.001) factors and adolescent reproductive health withno significant relationship discovered between the reproductive health of adolescents and parent communication (p=0.655), teacher communication (p=0.833), and sources of information (p=0.532). The most influencing factor associated with reproductive health in adolescent girls Islamic boarding school was peer communications (p=0.001). In conclusions, reproductive health problem in Islamic boarding school remains high with inadequate knowledge of reproductive health and low attitude towards reproductive health with peer communication as the most influencing factor. [MKB. 2015;47(2):77–83]Key words: Adolescent reproductive health, attitudes, environment knowledge, Islamic boarding school DOI: 10.15395/mkb.v47n2.457